Dietary and Supplemental Menaquinones Accumulate in Liver and Feces of C57BL6 Mice (P06-006-19). (13th June 2019) - Ellis, Jessie; Fu, Xueyan; Karl, J Philip; Hernandez, Christopher; Mason, Joel; Booth, Sarah
Abstract: Objectives: Vitamin K (VK) exists in multiple forms. Plant-based phylloquinone (PK) is considered the predominant dietary VK form. However, recent studies have shown bacterially-produced menaquinones (MKn; n = number of prenyl units in side chain) are prevalent in food such as dairy, fermented products, and meat, including pork. It is unknown if dietary MKn are absorbed and metabolized. The objective of this study was to compare MKn concentrations in blood, liver, and feces of mice given purified and food-based MKn to mice fed a VK-deficient (VKD) diet. Methods: Thirty male and 30 female 8-week old C57BL6 mice were acclimated on a VKD diet for 4 weeks and then maintained on VKD diet, or given a diet containing dietary MK9 (VKD + MK9), or pork (24% of diet, VKD + pork) for 4 weeks. VK forms in diets, blood, liver, and feces were measured using LC-MS. Within each sex, Kruskall-Wallis rank-sum tests were used to compare VK concentrations in VKD + MK9 mice to VKD mice, and to compare VKD + pork mice to VKD mice. VK concentrations are reported as mean ± SD (diets) or geometric mean ± SEM. Significance was set at α = 0.05. Results: The VKD diet contained 20.6 ± 1.9 ng PK/g diet; the VKD + MK9 diet contained PK (9.2 ± 1.6 ng/g) and MK9 (3820 ± 600 ng/g); and the VKD + pork diet contained PK (11.1 ± 0.6 ng/g), MK4 (38.5 ± 7.8 ng/g), MK9 (34.7 ± 9.8 ng/g), and MK10 (33.2 ± 10 ng/g). Liver MK9 was higher in the VKD + MK9 group than the VKD group (males: 16.8 ± 3.5 vs 3.3 ± 1.1 pmol/g, p = 0.002; females: 192 ± 26 vs 2.4 ± 3.1 pmol/g, p = 0.0001). Liver MK10 was higher in the VKD + pork group than the VKD group (males: 22.9 ± 8.0 vs 5.6 ± 1.3 pmol/g, p = 0.0007; females: 19.5 ± 5.0 vs 6.2 ± 4.0 pmol/g, p = 0.01). In feces, MK9 was higher in the VKD + MK9 group as compared to the VKD group (males: 3460 ± 430 vs 213 ± 56 pmol/g; females: 5360 ± 500 vs 344 ± 84 pmol/g, both p = 0.002). MK6 was greater in the VKD group than the VKD + pork group (males: 828 ± 210 vs 279 ± 49 pmol/g, p = 0.009; females: 679 ± 143 vs 404 ± 57 pmol/g, p = 0.04). No MKn forms were detected in blood. Conclusions: MKn forms in liver reflect dietary MKn intake. Fecal MKn partially reflect intake, but presence of fecal forms absent in the diet suggests fecal MKn also reflect production by the gut microbiota. Funding Sources: Supported by the USDA ARS CA 58-1950-7-707 and the Iowa Pork Producers Association.